UPAYA BADAN PENGUSAHAAN BATAM DALAM MENGEMBANGKAN INDUSTRI PERKAPALAN ASING DI BATAM - Sari, Emi Antika; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research analyzes the efforts of the Badan Pengusahaan Batam (BP Batam) to develop the foreign shipping industry in Batam City. The city of Batam, which is located in a strategic geographical area, encourages rapid economic growth compared to other cities in Indonesia, especially in the shipping industry, which invites foreign investors to invest capital, one of which is through Foreign Direct Investment (FDI). The theory used in this research is international economic policy. International economic policy is a variety of efforts made by governments to regulate national economic life in order to achieve certain goals. The author uses data collection techniques through field research, namely interviews with relevant sources in this research. This research shows several efforts made by BP Batam to develop the shipping industry in Batam, including by building several infrastructure such as the construction of the Yos Sudarso road, following up on allegations of illegal levies, as well as changing the Batam Authority to become BP Batam which focuses more on infrastructure development, supports free trade. BP Batam was given broader authority in licensing through an online system. Through various efforts carried out by BP Batam, this research shows that there is an economic improvement in the shipping sector with an increase in labor absorption in a number of foreign shipping companies in Batam. Keywords: Shipping Industry, BP Batam, foreign investors